2012
DOI: 10.1073/pnas.1216922110
|View full text |Cite
|
Sign up to set email alerts
|

p53 cooperates with DNA methylation and a suicidal interferon response to maintain epigenetic silencing of repeats and noncoding RNAs

Abstract: Large parts of mammalian genomes are transcriptionally inactive and enriched with various classes of interspersed and tandem repeats. Here we show that the tumor suppressor protein p53 cooperates with DNA methylation to maintain silencing of a large portion of the mouse genome. Massive transcription of major classes of short, interspersed nuclear elements (SINEs) B1 and B2, both strands of near-centromeric satellite DNAs consisting of tandem repeats, and multiple species of noncoding RNAs was observed in p53-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
261
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(288 citation statements)
references
References 61 publications
24
261
2
1
Order By: Relevance
“…Endogenous dsRNA species are some of the primary activators of the interferon response (Leonova et al , 2013; Mannion et al , 2014; White et al , 2014; Chiappinelli et al , 2015; Liddicoat, 2015; Roulois et al , 2015; Goel et al , 2017). Recent studies showed transcriptional activations of the ERVs triggered by several anti‐tumor drugs, which in turn resulted in ERV‐originated dsRNA accumulation, potent interferon responses, and significant tumor inhibition (Chiappinelli et al , 2015; Roulois et al , 2015; Goel et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous dsRNA species are some of the primary activators of the interferon response (Leonova et al , 2013; Mannion et al , 2014; White et al , 2014; Chiappinelli et al , 2015; Liddicoat, 2015; Roulois et al , 2015; Goel et al , 2017). Recent studies showed transcriptional activations of the ERVs triggered by several anti‐tumor drugs, which in turn resulted in ERV‐originated dsRNA accumulation, potent interferon responses, and significant tumor inhibition (Chiappinelli et al , 2015; Roulois et al , 2015; Goel et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…But such LTRs are highly involved in the emergence of new regulatory networks, such as the origin of the placenta (Bièche et al 2003;Chuong et al 2013;Emera and Wagner 2012;Harris 1998;Nakagawa et al 2013) (re-regulating 1500 genes) Lynch et al 2011Lynch et al , 2012 or in the African primates where alteration of 320,000 LTR p53 binding sites occurred onto the p53 cell cycle control network (Wang et al 2007). These primate p53 network changes also relate to (co-operate with) changes in brain specific microRNAs (Le et al 2009), alterations to DNA methylation involved in controlling SINE-derived RNA transcription (Leonova et al 2013), as well as Alu-derived transcription (Zemojtel et al 2009 In proposing the qs-c concept, it was argued that agent diversity (not errors) was essential for the capacity of a collective of RNA agents to function co-operatively (Villarreal and Witzany 2013b). Thus, an identity group of sub-functional RNA agents would be the predecessors of RNA-based life (not a functioning individual).…”
Section: Retroviral Network Regulate Evolution and Developmentmentioning
confidence: 97%
“…Therefore, we included a DNA-demethylating agent, 5-aza-2 0 -deoxycytidine (5-AZA), which was recently shown to be an effective chemotherapeutic agent in satellite DNA overexpressing cells. 28 Interestingly, we discovered that only WT PTEN cells had reduced sensitivity to 5-AZA (Fig. 4F).…”
Section: C-terminal Truncated Pten Mutant Does Not Function As a Tumomentioning
confidence: 99%